Natural Progression and Symptomatic Management of Tarsal-Carpal Coalition Syndrome: A Case Report. Issue 4 (27th October 2021) - Berg, Ari R.; Pletcher, Beth A.; Edobor-Osula, O. Folorunsho
Abstract : Case: Tarsal-carpal coalition syndrome (TCCS) is a disorder identified by fusion of the carpals, tarsals, and phalanges of the hands and feet. We describe a case of an 11-year-old girl who has been followed at our outpatient clinic from the age of 8 months. Conclusion: Although patients with TCCS can experience a wide range of symptoms, the primary complaint arises from the foot deformity and associated pain. Using advanced imaging such as 3D computed tomography reconstruction and genetic testing, this report details the clinical, genetic, and radiographic characteristics of the disorder. We highlight the natural progression and symptomatic management of TCCS.